PENGARUH STRUKTUR GOOD CORPORATE GOVERNANCE TERHADAP KINERJA PERUSAHAAN DAN MANAJEMEN LABA - Dwi Wahyuningsih (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2020)
The issue of this research is the importance of good corporate governance as a tool to determine the quality of company performance. The long-term goal to be achieved is to analyze how the Structure of Good Corporate Governance which is proxied by the Board of Commissioners, Independent Commissioners, Institutional Ownership, Managerial Ownership and Audit Committees affect Company Performance. Furthermore, testing is done to make a prediction model of Good Corporate Governance that affects company performance with Profit Management as mediation / intervening.Path analysis with 2S OLS, sampling using a purposive sampling method, is the method used to analyze the data used is a with criteria for companies manufacturing consumer goods industry sectors listed on the Stock Exchange in 2010-2015. The type of data is secondary data sourced from annual financial statements.The results showed that the first model of institutional ownership and audit committee affected the company's performance, the second model of the board of commissioners, independent commissioners, institutional ownership and audit committee affected earnings management and the third model of earnings management did not affect the company's performance. Earnings management is not able to mediate the effect of the structure of Good Corporate Governance on company performance.The findings of this study indicate that more than 92% of manufacturing companies in the consumer goods industry sector in 2010-2015, did earnings management by way of income smoothing.